How do students become self-directed learners in the EFL flipped-class pedagogy? A study in higher education - Zainuddin, Zamzami; Habiburrahim, H.; Muluk, Safrul; Keumala, Cut Muftia (Universitas Pendidikan Indonesia, 2019)
The purpose of this study was to identify the impact of implementing a Learning Management System (LMS) ‘TES BlendSpace’ to promote students’ self-directed learning in EFL flipped-class instruction. For the data collection procedure, an individual interview with ten undergraduate students from an Indonesian college was conducted to demonstrate the potential impacts of the LMS in students’ self-directed learning abilities. The observation of students’ learning activities on the TES BlendSpace was also recorded to support the interview data. The LMS was adopted to distribute and receive information. Thus, the students were able to monitor learning activities, learn the contents before coming to class, evaluate the learning process, and interact with others outside of class hours. The finding of this study suggests that the LMS TES BlendSpace is recommended to be performed in teaching EFL for higher education in Indonesia. It offers students’ occasion to practice and enhances their listening, writing, reading and vocabulary skills in and out-of-class times. It also prepares students to get ready for classroom activities in terms of conversations and speaking skills. The further use of the LMSs should become often-visited sites by students for learning activities and replacing other non-educational favorite websites. The finding of this study indicates that the students’ online culture was predominantly formed by the interesting contents posting on the LMS, especially the video lectures and an easy way to use. Additionally, instructors should develop activities in and around the LMS with a number of benefits and rewards. Hence, the students will be motivated to log in the LMS for learning purposes.